Aryl hydrocarbon receptor antagonism mitigates cytokine-mediated inflammatory signalling in primary human fibroblast-like synoviocytes. Issue 10 (24th January 2013) - Lahoti, Tejas S; John, Kaarthik; Hughes, Jarod M; Kusnadi, Ann; Murray, Iain A; Krishnegowda, Gowdahalli; Amin, Shantu; Perdew, Gary H
Abstract : Objectives: Rheumatoid Arthritis (RA) is a chronic inflammatory disease of unclear aetiology, which is associated with inflamed human fibroblast-like synoviocytes (HFLS). Epidemiological studies have identified a positive correlation between tobacco smoking (a rich source of aryl hydrocarbon receptor (AHR) agonists) and aggressive RA phenotype. Thus, we hypothesise that antagonism of AHR activity by a potent AHR antagonist GNF351 can attenuate the inflammatory phenotype of HFLS-RA cells. Methods: Quantitative PCR was used to examine IL1B-induced mRNA expression in primary HFLS-RA cells. A structurally diverse AHR antagonist CH223191 and transient AHR repression using AHR small interfering RNA (siRNA) in primary HFLS-RA cells were used to demonstrate that effects observed by GNF351 are AHR-mediated. The levels of PTGS2 were determined by western blot and secretory cytokines such as IL1B and IL6 by ELISA. Chromatin-immunoprecipitation was used to assess occupancy of the AHR on the promoters of IL1B and IL6 . Results: Many of the chemokine and cytokine genes induced by IL1B in HFLS-RA cells are repressed by co-treatment with GNF351 at both the mRNA and protein level. Pretreatment of HLFS-RA cells with CH223191 or transient gene ablation of AHR by siRNA confirmed that the effects of GNF351 are AHR-mediated. GNF351 inhibited the recruitment of AHR to the promoters of IL1B and IL6 confirming occupancy of AHR at these promoters is required for enhanced inflammatory signalling. Conclusions: These data suggest that AHR antagonism may represent a viable adjuvant therapeutic strategy for the amelioration of inflammation associated with RA.